Chinese High-speed Railway: Efficiency Comparison and the Future - Li, Weidong; Hilmola, Olli-Pekka; Wu, Jianhong (Promet - Traffic&Transportation, 2019)
High-speed railway (HSR) network building was initiated in China in the early 2000s, and full-scale construction began several years later as a larger use phase started in 2008. Thereafter, the expansion speed has been impressive. Network investment could be considered as a success, if evaluating the amount of high-speed railway usage already during the expansion phase. The diffusion models built in this research show that expansion in the network and growth of the passengers will continue at least until the following decade. The performance is evaluated in terms of DEA efficiency model. It is shown that efficiency started from very low levels, but it has been increasing together with the expansion of HSR network. Currently, the efficiency is near the level of the leading European High-speed (HS) countries (Germany and France). However, it is projected with linear model and by Bass diffusion models that the efficiency will reach Japanese and South Korean standards in the next decade. A somewhat larger network length with smaller relative growth of passengers, but with a higher growth of passenger-km seems to be able to reach even the frontier efficiency.